Ultrasound-assisted synthesis of organotin compounds and their application as luminescent dye in silk fibroin scaffolds - Lara-Cerón, Jesús A.; Jiménez-Pérez, Víctor M.; Molina-Paredes, Areli A.; Ochoa, María E.; Sábio, Rafael M.; Amaral, André C.; da Silva, Robson R.; Ribeiro, Sidney J.L. [UNESP]; da S. Barud, Hernane; Muñoz-Flores, Blanca M. (My University, 2020)
In this work, we report the green synthesis of four luminescent organotin compounds 1–4 derived from amino acid Schiff bases (1: Naph-Trp-SnPh2, 2: Naph-Tyr-SnBu2, 3: Naph-Tyr-SnPh2, 4: Naph-Phe-SnPh2), obtained by ultrasound-assisted synthesis in short time (~20 min) and good yields (>95%). The molecular structure proposed in solution (1H and 119Sn NMR) was confirmed by X-ray diffraction study for compound 1 where the tin atom resides in trigonal bipyramid geometry. Luminescent silk fibroin scaffolds (SF 1–4) were elaborated with organotin compounds by freeze-drying technique. Photophysical properties of organotin compounds and scaffolds were obtained in solid state, observing bathochromic behaviors in tyrosine derived compounds, suggesting that the tyrosine produce supramolecular interactions across the –OH group that change the fluorescent properties. Scaffolds 1–4 were characterized by FTIR, XDR, TG/DTG, and SEM analysis. In addition, cytotoxic analysis of SF 1 presents high cellular viability, which could be applied as a scaffold in tissue engineering.
Keywords: Fluorescence; Organotin; Scaffold silk fibroin; Ultrasound-assisted synthesis; X-ray